Effect of protein level in prepartum diets on postpartum performance of dairy cows - Park, A. F.; Titgemeyer, Evan C.; Scheffel, Michael V.; Meyer, M. J.; Shirley, John E. (Kansas Agricultural Experiment Station and Cooperative Extension Service, 2011)
Seventy-five Holstein cows were used in a randomized complete block design to determine the level of dietary protein required to support metabolic functions and maintain body reserves during the periparturient period and subsequent lactation. Cows fed the 14.7% protein diet prepartum had a more ideal body condition score during the entire prepartum and postpartum periods. During the first 90 days of lactation, few consistent differences occurred among prepartum diets for milk production, but the response to rbST was greatest for cows fed 11.7, 13.7 or 14.7% protein prepartum. Full 305-day lactation records showed the most milk, fat, and protein for cows consuming 13.7 or 14.7% protein prepartum. Results of our study indicate that using 13.7 to 14.7% crude protein with approximately 45% undegradable protein in the close-up diet for dairy cattle produces beneficial outcomes during the subsequent lactation.
Keywords: Dairy; Prepartum; Protein; Dairy cows